STAGES OF PLANNING A PLOT FOR CONSTRUCTION OF A COUNTRY HOUSE - Berezovetska І.; Dudiak Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The article explores key aspects of landscape planning, architecture, and environmental design as contemporary approaches to shaping public and private spaces. It analyzes current challenges and opportunities for architecture and design professionals aimed at creating aesthetically appealing, functional, and environmentally balanced landscapes. The literature presents three terms: landscape planning, landscape architecture, and landscape design. Landscape design is closely related to landscape architecture. Landscape design, planning, and organizing a plot for constructing a private house are crucial in creating an attractive and functional space around our homes. It not only enhances the house’s exterior appearance but also creates a comfortable and safe environment for leisure and outdoor activities, providing aesthetic enjoyment. There are countless options for landscaping – from blooming multicolored flower beds and well-kept lawns to graceful pergolas or garden swings, and even water features like fountains or streams. Each element can be positioned to create a unique atmosphere. The selection of each detail is an opportunity to translate ideas into reality, creating a special corner for relaxation and enjoyment of nature, where each plant and object has its place and contributes to harmony and aesthetic satisfaction. In this way, it is possible to create an atmosphere that corresponds to the preferences and needs of the homeowners.